Contribution of increased oral bioavailability and reduced nonglomerular renal clearance of digoxin to the digoxin-clarithromycin interaction - Rengelshausen, Jens; Göggelmann, Christoph; Burhenne, Jürgen; Riedel, Klaus-Dieter; Ludwig, Jochen; Weiß, Johanna; Mikus, Gerd; Walter-Sack, Ingeborg; Haefeli, Walter E. (British journal of clinical pharmacology, 2003)
A clinically important interaction between the cardiac glycoside digoxin and the antibiotic clarithromycin has been suggested in earlier reports. The aim of this study was to investigate the extent of the interaction and the relative contribution of different mechanisms.